Geoprocessamento e planejamento urbano: uma análise espacializada das creches de período integral no município de Ananindeua – PA - FURTADO, Layse Gomes (2019)
This work aimed to made a socio-spatial analysis about the child care centres in the Ananindeua City (Municipality), State of Pará, Brazil, and its acessibility across the neighborhoods. The methodology was composed by survey data collection, data crossing, mainly IBGE demographic census of IBGE (2010th year). It was possible carry out the socioeconomic analysis, acessibility analysis and topological one in QGIS 2.18, using geoprocessing tools. The results of the research highlight the identification of priority areas for the installation of new child care centres in the same neighborhoods, as well as to verify the greater adequate accessibility index, ensuring the growth of the number of children assisted by this public service. The socio-spatial analysis provides the necessary support for the validation of urban studies, or investigative studies about cities for urban planning, in particular, the municipal education system.